FACTORS INFLUENCING CUSTOMER’S INTENTION IN PAYING TRANSACTION USE E-MONEY (Empirical Study at Economic and Business Faulty Brawijaya University Student) - Hapsari, Yolanda Indriana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The objectives of this research is to examine the factors that influence the customerâ€™s in the transaction using electronic money with modified models of Technology Acceptance Model (TAM). Variables in this research using perceived usefulness, perceived ease of use, perceived of security, trust and intention to use. The population in this research is all college student in FEB UB active status in the odd semester of the academic year 2015/2016. Researchers used nonprobability sampling for determine sample. Samples in this research as many as 305 students of FEB UB students but only 184 that can be sampled because there is bias in data collection. The results of this research shows that constructs perceived usefulness and trust affect the intention to use electronic money. While the ease of use and security construct did not affect intention to use electronic money. It means that the intention to use electronic money is affected by the variable perceived usefulness andtrust. The implications this research can be used by publishers who provide electronic money products to better prioritize factors that affect the intention of individuals to use electronic money so that people believe that the electronic money efficient to use. Â Keywords: Students of FEB UB,Intention to Use Electronic Money, Perceived Usefulness.